RESPONSE OF VEGETATIVE GROWTH FOR THE TREATMENT OF ORGANIC NUTRIENT AND CALCIUM CHLORIDE FOR GERBERA PLANT Gerbera jamesonii - & Majeed, Jawad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in the lath house, Horticultural Department, College of Agriculture – University of Baghdad- Jadriya during the spring and autumn seasons 2015 to investigate the influence of humic acid spray and calcium chloride spray on f “Yanara” gerbera cultivar.  This study included two factors; humic acid spray (H) and calcium chloride spray (Ca). The first factor four levels were used, 0, (H0), 5 (H5), 7.5 (H7.5) and 10 (H10) ml.L-1 and four levels of calcium chloride, 0 (Ca0), 50 (Ca50), 100 (Ca100) and 150 (Ca150) mg.L-1. Each treatment replicated three times with a factorial experiment using RCBD. Five plants in experimental unit and the number of plants used was 240 trees. The experimental results showed that humic acid at 10 ml.L-1 and calcium chloride at 150 mg.L-1 (Ca150H0) significantly gave the highest leaves number of 11.20 and 11.47 leaves, the highest leaf area of 195.21 and 210.25 cm2, the highest plant dry weight of 16.92 and 17.95gm, the highest leaf nitrogen content of 2.50 and 2.45 %, highest leaf phosphor content of 0.37 and 0.44% and the highest leaf calcium content of 3.17 and 3.45% for both seasons, respectively. The lowest value of these parameters was found in the control (Ca0H0) treatment. It could be concluded of this experiment that the humic acid at level H10 and calcium chloride at level Ca150 improved vegetative characteristics and leaf mineral content gerbera plant cv. Yanara